An analysis of fungal exudate and carbon use efficiency - Nübl, Laura (Jihočeská univerzita, 2022)
The exometabolome of various fungal functional guilds was investigated as part of the below-ground carbon flux. This thesis addresses the incorporation and exudation of carbon by individual, axenic fungal cultures, with a focus on developing a protocol for characterisation and identification of those compounds.
An analysis of fungal exudate and carbon use efficiency
Keywords: fungi; carbon cycle; isotopes; GC-MS; functional guilds; carbon use efficiency; antioxidant assay; carbon flux; metabolomics; exudate; fungi; carbon cycle; isotopes; GC-MS; functional guilds; carbon use efficiency; antioxidant assay; carbon flux; metabolomics; exudate